Feasibility of reduced iodine loads for vascular assessment prior to transcatheter aortic valve implantation (TAVI) using spectral detector CT - Schuppert, Christopher; Salatzki, Janek; André, Florian; Riffel, Johannes; Mangold, David Lukas; Melzig, Claudius; Hagar, Muhammad Taha; Kauczor, Hans-Ulrich; Weber, Tim; Rengier, Fabian; Do, Thuy (Diagnostics, 2024)
Reduced iodine loads for computed tomography (CT)-based vascular assessment prior to transcatheter aortic valve implantation (TAVI) may be feasible in conjunction with a spectral detector CT scanner. This prospective single-center study considered 100 consecutive patients clinically referred for pre-TAVI CT. They were examined on a dual-layer detector CT scanner to obtain an ECG-gated cardiac scan and a non-ECG-gated aortoiliofemoral scan. Either a standard contrast media (SCM) protocol using 80 mL Iohexol 350 mgI/mL (iodine load: 28 gI) or a body-mass-index adjusted reduced contrast media (RCM) protocol using 40-70 mL Iohexol 350 mgI/mL (iodine load: 14-24.5 gI) were employed. Conventional images and virtual monoenergetic images at 40-80 keV were reconstructed. A threshold of 250 HU was set for sufficient attenuation along the arterial access pathway. A qualitative assessment used a five-point Likert scale. Sufficient attenuation in the thoracic aorta was observed for all patients in both groups using conventional images. In the abdominal, iliac, and femoral segments, sufficient attenuation was observed for the majority of patients when using virtual monoenergetic images (SCM: 96-100% of patients, RCM: 88-94%) without statistical difference between both groups. Segments with attenuation measurements below the threshold remained qualitatively assessable as well. Likert scores were ‘excellent’ for virtual monoenergetic images 50 keV and 55 keV in both groups (RCM: 1.2-1.4, SCM: 1.2-1.3). With diagnostic image quality maintained, it can be concluded that reduced iodine loads of 14-24.5 gI are feasible for pre-TAVI vascular assessment on a spectral detector CT scanner.
Gesehen am 30.09.2024